1987
DOI: 10.1136/gut.28.4.382
|View full text |Cite
|
Sign up to set email alerts
|

Life prospects and quality of life in patients with Crohn's disease.

Abstract: DenmarkSUMMARY A regional prevalence group of 106 patients with Crohn's disease were interviewed about their familial, social, and professional conditions. The results were compared with results from similar interviews of an age and sex matched control group of 75 previously healthy patients admitted to the hospital for acute diseases of less than 28 days' duration. An equal percentage of the patients and the controls were married (67% vs 71%) and had become parents (68% vs 79%). The number of children was sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 4 publications
1
66
0
Order By: Relevance
“…Furthermore, females have greater disease-related concerns and worries about being treated differently as a result of their disease (31) and are also more likely to report concerns related to attractiveness and body image (8,28) . Previous studies have shown that HRQOL is significantly impaired by work disability (2,3,17,42) . The work disability rates of IBD patients range between 1.3% and 34% (45) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, females have greater disease-related concerns and worries about being treated differently as a result of their disease (31) and are also more likely to report concerns related to attractiveness and body image (8,28) . Previous studies have shown that HRQOL is significantly impaired by work disability (2,3,17,42) . The work disability rates of IBD patients range between 1.3% and 34% (45) .…”
Section: Discussionmentioning
confidence: 99%
“…In general, IBD is associated with high levels of perceived strain and social stress, although outcomes on measurable aspects of social and occupational outcome are comparable to community controls [1, 2, 3, 4]. Students with IBD report similar academic success to their peers in spite of missing more school days [27, 28].…”
Section: Coping In Ibdmentioning
confidence: 99%
“…The central clinical and research question in choosing appropriate psychosocial interventions is: ‘Which intervention for which person under which circumstances at which time?’ In addressing this question, the mental health professional who serves patients with ulcerative colitis (UC) and Crohn’s disease (CD) is met with a complex challenge due to several factors which include: (1) a high degree of perceived need for psychosocial support of patients from the patients themselves, their families and professionals in the absence of strong empirical evidence of greatly compromised functional outcomes overall [1, 2, 3, 4], (2) a prejudice that people with inflammatory bowel disease (IBD) are ‘difficult patients’ in the absence of strong empirical evidence that in general IBD is associated with maladaptive personality traits [5, 6], (3) a persisting belief among patients that life stress is a major contributor to disease course [7], in the absence of strong empirical evidence to support this hypothesis [5, 6], and (4) the inconsistent psychosomatic literature which suggests both benefit and harm from psychosocial interventions in this population without clear evidence-based guidelines regarding strategies for patient selection and intervention type.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD) is a chronic inflammatory condition of the gastrointestinal tract resulting in a marked decrease in health related quality of life (HRQoL) [1][2][3][4] . Despite advances in pharmacologic and surgical treatment strategies, patient understanding and knowledge of their disease varies widely [5] .…”
Section: Introductionmentioning
confidence: 99%